ANALISIS RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PADA PT. INDOFOOD SUKSES MAKMUR TBK - Danayanti Manik; Yossi Fadliy; Puja Rizqy Ramadhan (Ensiklopedia Education Review, 2022)
This study aims to analyze the profitability ratios, liquidity ratios, solvency ratios and activity ratios at PT. Indofood Sukses Makmur Tbk, this type of research is qualitative and uses secondary data in the form of financial reports for 2016 – 2020. The results show that the profitability ratios (NPM, ROA and ROE) are below industry standards. CR liquidity ratios are below industry standards. and QR is above the industry standard. The solvency ratio of DAR is above the industry standard and the DER ratio is below the industry standard. Activity ratio The receivables turnover ratio is below the industry standard and the working capital turnover ratio is below the industry standard.Keywords: Profability, Liquidity, Slovability, Activity.